An Efficient Strategy Combining Immunoassays and Molecular Identification for the Investigation of Fusarium Infections in Ear Rot of Maize in Guizhou Province, China - Shang, Guofu; Li, Shuqin; Yu, Huan; Yang, Jie; Li, Shimei; Yu, Yanqin; Wang, Jianman; Wang, Yun; Zeng, Zhu; Zhang, Jingbo; Hu, Zuquan (Frontiers in Microbiology, 2022)
Fusarium is one of the most important phytopathogenic and mycotoxigenic fungi that caused huge losses worldwide due to the decline of crop yield and quality. To systematically investigate the infections of Fusarium species in ear rot of maize in the Guizhou Province of China and analyze its population structure, 175 samples of rotted maize ears from 76 counties were tested by combining immunoassays and molecular identification. Immunoassay based on single-chain variable fragment (scFv) and alkaline phosphatase (AP) fusion protein was first employed to analyze these samples. Fusarium pathogens were isolated and purified from Fusarium-infected samples. Molecular identification was performed using the partial internal transcribed spacer (ITS) and translation elongation factor 1α (TEF-1α) sequences. Specific primers were used to detect toxigenic chemotypes, and verification was performed by liquid chromatography tandem mass spectrometry (LC–MS/MS). One-hundred and sixty three samples were characterized to be positive, and the infection rate was 93.14%. Sixteen species of Fusarium belonging to six species complexes were detected and Fusarium meridionale belonging to the Fusarium graminearum species complex (FGSC) was the dominant species. Polymerase chain reaction (PCR) identification illustrated that 69 isolates (56.10%) were potential mycotoxin-producing Fusarium pathogens. The key synthetic genes of NIV, NIV + ZEN, DON + ZEN, and FBs were detected in 3, 35, 7, and 24 isolates, respectively. A total of 86.11% of F. meridionale isolates carried both NIV- and ZEN-specific segments, while Fusarium verticillioides isolates mainly represented FBs chemotype. All the isolates carrying DON-producing fragments were FGSC. These results showed that there are different degrees of Fusarium infections in Guizhou Province and their species and toxigenic genotypes display regional distribution patterns. Therefore, scFv-AP fusion-based immunoassays could be conducted to efficiently investigate Fusarium infections and more attention and measures should be taken for mycotoxin contamination in this region.